Profile morphology of Fiber Bragg Gratings during initial cracking: a case study on proof load testing of an arch spandrel segment - Poh, Abdul Halim; Abu Hassan, Muhammad Rosdi; Abu Bakar, Muhammad Hafiz; Mahamd Adikan, Faisal Rafiq; Moghavvemi, Mahmoud (Institute of Electrical and Electronics Engineers, 2022)
The occurrence of “initial cracking” in bridges during proof load testing (PLT) is a relatively brief procedure, taking only a few hours. Its long-term effects may play a role in future understanding of the future behavior of the bridge. In this paper, we document a brief period of PLT via interrogation an FBG sensor (central wavelength of 1554.2nm) in an arch spandrel bridge which was constructed before opening for public use. We logged data before, during and after the load testing session using a broadband light source and a tunable laser. Based on the data, we discuss the wavelength shift profiles, and its morphology during the period. The main findings of this study reveals that the initial cracking procedure exhibits unique behavior indicated by the sudden changes of the FBG spectra, though exhibiting some latency. Prior to the PLT session (acclimatizing window), there were already perturbations to structure causing up to 0.2nm shift in the FBG central wavelength, while during the PLT session, the central wavelength snapped between ~1554.1nm to ~1554.3nm. The fluctuations stopped after the PLT, confirmed with tunable lasers’ profile as well. These findings demonstrates that not only initial crackings most likely can be detected via PLT, but it may also occur before the PLT exercise itself due to its own intrinsic load.